PENGARUH PENERAPAN PRINSIP GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PADA BADAN USAHA MILIK DAERAH PROVINSI RIAU - Pirdaus, Padli; Aristi, Mentari Dwi; Ahyaruddin, Muhammad (LPPM Universitas Bina Bangsa, 2025)
This research was motivated by problems that occurred at the Main Branch Office of PT Permodalan Ekonomi Rakyat regarding irregularities in receiving principal and interest installments on seven credit agreements in the names of three business partners related to credit agreements. The Effect of Implementing Good Corporate Governance Principles on Financial Performance in Regionally Owned Enterprises in Riau Province. The population is 58 people. Sampling in this research used a purposive sampling method. The data used is primary data. The data collection techniques used were field research and distributing questionnaires. The data analysis method used is multiple linear regression. The results of this research show that the effect of implementing the principles of good corporate governance on financial performance in regionally owned enterprises in Riau Province.